Using the principal model in the preparation of athletes qualified in short-track - Kugaevskij Sergej Aleksandrovich (Kharkov National Pedagogical University, 2011)
The materials on the level of development problems of modeling training process in short-track. Analysis of materials preparation and construction of the training process and a change of the training loads. Constructed basic model training process. Shown to the dynamics of change in functional status of athletes in the training season. Consider ways to optimize the training process using fundamental models. Found that the proportion of aerobic orientation in the annual cycle varies slightly. Vary significantly and change the relationship between stress and mixed anaerobic nature of energy.